POLYDRUG ABUSE WITH HEPATITIS C VIRUS POSITIVITY IN A 17-YEAR-OLD MALE: A MULTIDISCIPLINARY CLINICAL CHALLENGE - Aparna V; Kirthika V; Dr.M. Dheenadhayalan; Dr.K. Karthickeyan; Dr. P. Shanmuga Sundaram; Dr. M.K. Sundar Sri (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Polydrug abuse among adolescents is a pressing public health crisis, exacerbated by concurrent infections such as hepatitis C virus (HCV), which compound clinical complexity and management challenges. This report describes a 17-year-old male with a one-year history of polydrug abuse—encompassing alcohol, tobacco, cannabis, and intravenous drug use—who presented with somatic complaints, chest pain, and sleep disturbances. Mental status assessment revealed significant anxiety and difficulties in rapport-building. Laboratory investigations demonstrated profound hepatic injury (SGPT: 1055 U/L, SGOT: 1640 U/L) and confirmed HCV infection (Anti-HCV: Reactive, HCV RNA: 19.74 IU/mL). Management was multidisciplinary, integrating psychiatric care (risperidone, clonazepam), direct-acting antiviral therapy (sofosbuvir and daclatasvir), hepatoprotective agents (ursodeoxycholic acid, B.liv forte), and comprehensive counseling on abstinence and lifestyle modification.The case underscores the critical need for early identification and integrated, guideline-based management in adolescent polydrug users with HCV. Multidisciplinary collaboration involving mental health, infectious disease, and pharmacy services is essential to optimize clinical outcomes, reduce morbidity, and support sustained recovery1. Continued follow-up is recommended to monitor for relapse and ensure long-term well-being.